Energies of complements of unitary one-matching bi-Cayley graphs over commutative rings. Issue 20 (19th December 2022) - Yang, Jinxing; Liu, Xiaogang; Wang, Ligong
Abstract : In this paper, we determine the energies of complements of unitary one-matching bi-Cayley graphs over finite commutative rings. We also determine the energies of some one-matching bi-gcd-graphs as well as the energies of complements of some one-matching bi-gcd-graphs, which are generalizations of unitary one-matching bi-Cayley graphs.